Factors Affecting the Allocation of Working Time for Corn Farmers in Gorontalo District - Isran Jafar; Amir Halid; Zulzain Ilahude (Universitas Muhammadiyah Palu, 2024)
The aim of this research is to find out the potential time of labor of corn farmers used for productive activities by corn farmers. Examine the factors that influence the allocation of farmer working time to corn farming. This research is quantitative research. The data source in this study is secondary data in the form of primary data from the distribution of questionnaires to corn farmers. The data analysis technique used is multiple regression analysis. The results of this study indicate that the potential time of labor in the family on productive activities in the agricultural sector is more dominated by male labor, which is an average of 617.35 HKSP, the results of the parsial test found that the variable land area, wage level and education significantly influence the allocation farmer working time on corn farming. While for skills, type of workforce and land management/technology systems have no significant effect.